Innovations in global maternal health improving prenatal and postnatal care practices (Trending Topics Book Series (TTBS)., 2020)
"This book addresses the main issues facing women during pregnancy, childbirth, and the postpartum period. It also explores new techniques, tools, and solutions that can be used in a global capacity to support women regardless of their wealth or location"--Provided by publisher.